FINANCIAL AND INDUSTRIAL INVESTIGATIONS. - Andersen, Arthur (The Accounting Review, 1929)
Abstract For many years there have been investigations which lay outside the field of accounting and were aimed at showing and interpreting some of the more active factors of business. On the other hand, accountants have been used to examining the financial results of businesses with but little thought to the factors which have combined to produce these financial results. In many cases the analysis and interpretation of financial results in their relation to the going business has been left to the management, the accountant perhaps feeling that the full scope of his responsibility was discharged when he presented the approved balance sheet and results from operations statement. Business fundamentally is a complex structure, based on the three dominant elements of production, sales and finance, each of which is in itself complex. Management is no longer in its usual former position of sole stock ownership. It no longer deals with units so small that they can be effectively administered on the basis of personal knowledge and personal contacts. Its problems are as diversified as its operations, not only geographically, but also functionally.